Effects of alcohol (BAC 0.5 [per mille]) and ecstasy (MDMA 100 mg) on simulated driving performance and traffic safety - Veldstra, Janet L.; Skopp, Gisela; Jantos, Ricarda (Psychopharmacology, 2012)
Rational: An increasing number of fatal road-accidents have been reported in which ecstasy was found in the blood of drivers. Although, ecstasy is frequently found to have been used in combination with alcohol, studies on the acute effects of ecstasy co-administered with alcohol on driving performance are relatively rare.ObjectiveThe present study was designed to establish the extent of driver impairment as a consequence of ecstasy or combined ecstasy and alcohol use as compared to driving under the influence of 0.3‰, 0.5‰ and 0.8‰ alcohol. Furthermore, subjective performance was also assessed.ResultsAlcohol and ecstasy mainly influenced automated driving performance such as lateral and speed control. However, small to no effects of the substances were found on more complex driving behaviour. Overall, variance within the different driving measures was high especially when participants were treated with 3.4-methylenedioxy-methamphetamine (MDMA) and alcohol. Furthermore, equivalence testing showed that combined use may lead to impaired driving for some, but not all, drivers. Participants rated their own performance to be slightly worse than normal in both studies. Since driving was actually seriously deteriorated, this was a falsely positive assessment of their condition.ConclusionsThe dissociation between subjective perceptions and objective performance decrements are important notions for traffic safety since this may affect a driver’s judgement of whether or not it is safe to drive. For example, an intoxicated individual might decide to drive because the feelings of alertness caused by MDMA cloud the impairing effects of other drugs such as alcohol, thereby creating a potentially serious risk for traffic safety.